2021
DOI: 10.1101/2021.04.13.439617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Unilateral Transcranial Direct Current Stimulation on Unimanual Laparoscopic Peg-Transfer Task

Abstract: Introduction: Efficient training methods are required for laparoscopic surgical skills training to reduce the time needed for proficiency. Transcranial direct current stimulation (tDCS) is widely used to enhance motor skill acquisition and can be used to supplement the training of laparoscopic surgical skill acquisition. The aim of this study was to investigate the effect of anodal tDCS over the primary motor cortex (M1) on the performance of a unimanual variant of the laparoscopic peg-transfer task. Methods: … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The few studies to date vary not only according to their methodological rigour but also by the site of neurostimulation, the tasks experimenters evaluated and the metrics that were used to quantify performance. For example, stimulation has largely been administered over the prefrontal cortex [18] [19], primary motor cortex [20][21] [22] or supplementary motor area (SMA; [21]), with most manually evaluating basic metrics of performance including the time to complete the task [19] [23] or a score related to the number of errors made [18] [20][21] [24]. However, research highlighting the need for more robust and objective metrics to quantify surgical performance has shown that the inclusion of biomechanical measures such as instrument movement e ciency, velocity, and positioning can provide a more complete description of surgical skill [25][26] [27].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies to date vary not only according to their methodological rigour but also by the site of neurostimulation, the tasks experimenters evaluated and the metrics that were used to quantify performance. For example, stimulation has largely been administered over the prefrontal cortex [18] [19], primary motor cortex [20][21] [22] or supplementary motor area (SMA; [21]), with most manually evaluating basic metrics of performance including the time to complete the task [19] [23] or a score related to the number of errors made [18] [20][21] [24]. However, research highlighting the need for more robust and objective metrics to quantify surgical performance has shown that the inclusion of biomechanical measures such as instrument movement e ciency, velocity, and positioning can provide a more complete description of surgical skill [25][26] [27].…”
Section: Introductionmentioning
confidence: 99%